ANALISIS KOMPARATIF MODEL INTERPRETASI ISTILAH WARNA DALAM AL QUR’AN - Ruston Kumaini; Ahyat Habibi; Inanda Tsabithah Salsabila (Al-Majaalis : Jurnal Dirasat Islamiyah, 2023)
ABSTRACT This research investigates comparatively the translation model of the term color (لون) and its derivations in the holy Qur'an. In this case Arabic is the source language, while Indonesian and English are the target languages. This research is a descriptive-analytical research using a qualitative approach. The data analyzed were in the form of 33 words related to color terms which include: white, green, black, yellow, blue, and red. The data were then analyzed for their translation model into Indonesian in the Indonesian Koran (Kemenag RI version) and in the English Koran (Shaheeh International version). The basis for the translation analysis used by researchers is the Foreignization and Domestication approach proposed by Lawrence Venuti. The results of the analysis show that translation using the foreignization approach is more dominantly used by translators in the target language (TL), namely Indonesian and English compared to the domestication approach. This happens because translators prioritize the presence of source language culture to readers. Meanwhile, the domestication approach is applied by the translator if the target language does not have an equivalent form with the source language. Keywords: color terms, translation, foreignization, domestication